2012
DOI: 10.3177/jnsv.58.136
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Polyphenols and Pharmacological Analysis of Water and Ethanol-Based Extracts of Cultivated Agarwood Leaves

Abstract: Summary Mangiferin ( 3 ) and genkwanin 5-O -␤ -primeveroside ( 5 ) are the two major bioactive polyphenols with laxative property present in the extracts of agarwood ( Aquilaria sinensis ) leaves (AL). Here we developed an HPLC method to determine these bioactive components and four other major polyphenols in AL extracts and evaluated the pharmacological equivalence of organic and water extracts. Using mobile phase gradient conditions combined with UV detection at 330 nm, all six compounds were separated and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 3 publications
2
25
0
Order By: Relevance
“…This was enhanced by the use of heated water, thus improving extraction [21]. Although hydrophilic organic solvents (e.g., ethanol) are usually utilized to obtain these kinds of compounds [22], a pharmacological equivalency has been demonstrated between alcoholic extracts and those derived from infusions [23]. Therefore, flavonoids become bioavailable in humans due to the presence of functional chemical groups (e.g., hydrophilic hydroxyl and carbonyl) in their polycyclic structures [24].…”
Section: Discussionmentioning
confidence: 99%
“…This was enhanced by the use of heated water, thus improving extraction [21]. Although hydrophilic organic solvents (e.g., ethanol) are usually utilized to obtain these kinds of compounds [22], a pharmacological equivalency has been demonstrated between alcoholic extracts and those derived from infusions [23]. Therefore, flavonoids become bioavailable in humans due to the presence of functional chemical groups (e.g., hydrophilic hydroxyl and carbonyl) in their polycyclic structures [24].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been warranted with previous study indicated that Aquilaria species have pharmacological effect including in Alzheimer disease, diabetes mellitus and antioxidant [14]. This is followed by discovering laxative properties in Aquilaria leaves which believe contain active polyphenolic compound such as mangiferin and genkwanin 5-O-β-primeveroside [10,20]. Aligned with this, the antilipase activity of Aquilaria crude extracts is possibly related with existence of polyphenolic compounds.…”
Section: Research Articlementioning
confidence: 99%
“…The leaves of Aquilaria sp. are believed to have major polyphenolic compounds which can be used as herbal tea and showed a laxative [10][11][12], anti-bacterial [13], and anti-diabetic properties [7]. In addition, stem of A. subintegra has been reported as promising in Alzheimer therapy [14].…”
mentioning
confidence: 99%
“…have been reported in many studies (Nie et al 2009 ;Qi et al 2009 ;Feng and Yang 2012 ;Ito et al 2012 ;Cheng et al 2013 ;Xia et al 2013 ;Yu et al 2013 ;Tay et al 2014 ). Of the constituents studied, mangiferin and epigallocatechin gallate (EGCG) have been discussed the most.…”
Section: Introductionmentioning
confidence: 99%